Reuse of ablution water to improve peat soil characteristics for ornamental landscape plants cultivation - Radin Mohamed, Radin Maya Saphira; Abduh Algheethi, Adel Ali Saeed; Abdul Rahman, Junita; Mohd Kassim, Amir Hashim; Musa, Sabariah (EDP Sciences, 2017)
The present study aimed to reuse of ablution water for washing peat soil in order to reduce the concentrations of heavy metals in these soils which might effect negatively on the plant growth. The washing process design was similar to horizontal subsurface flow constructed wetlands (HSSFCW) consist of layers of peat and sand soil and surrounded by gravel on both sides. Strelitzia sp. was used to detect the presence negative effect of the washing process on the morphological characteristics of the plants. The physical and chemical characteristics of ablution water was examined before and after the washing process by using Inductively Couple Plasma- Mass Spectrometer (ICP-MS) Atomic Absorption Spectrometer (AAS). The characteristics of peat soil before and after the washing process were examined by using X-Ray Fluorescence (XRF). The results revealed that the percentage of FeO3in peat soil reduced from 45.80 to 1.01%. The percentage of SiO2 in sand soil dropped from 87.7 to 67.10%. Parameters of ablution water resulted from the washing process which including Biological Oxygen Demand (BOD5) and heavy metals have increased but still within the standard limits for the disposal of ablution water into the environment. No atrophy was observed in Strelitzia sp. leaves, indicating the ability of plant to grow normally. It can be concluded that the utilization of ablution water in the washing of peat soil has improve the characteristics of the soil without effect on their organic constitutes.